Chromatography of Particle Suspensions - Husain, Aamir (My University, 1980)
In recent years, a number of chromatographic techniques have been reported to measure the size of submicron particles. Little of the published work has dealt with the quantitative estimation of particle size, efforts, largely, having been directed in demonstrating the capability to resolve colloid peaks. Ability to make quantitative measurements is a prime requirement for any analytical tool and this is the problem that is addressed in this work.
Common to all the chromatographic techniques is the phenomenon of axial dispersion which disperses a colloid over a finite interval centered around its mean residence time or retention volume. The response to a pulse of monodispersed colloid is a bell shaped chromatogram, the shape of which along with the peak separation capability of the instrument, determine for a given detector, the type of analysis by which raw measured data have to be processed. The analysis may be of two types. The first, applies correction factors to moments calculated directly from the measured chromatogram to account for axial dispersion, while, the second approach allows a calculation of the moments of the diameter distribution of particles which at any instant occupy the detector cell. Besides developing the various methods for treating chromatographic data in detail, the problem of determining the response to a pulse of monodispersed colloid has been attempted. Experimentally, such information can be determined only with some difficulty, owing to the unavailability of very narrow distribution standards.
Experiments were conducted using a size exclusion chromatograph equipped with a turbidity detector. The performance of the turbidity detector was critically evaluated. A column calibration procedure has been attempted which minimises material loss, significantly reduces the extent of axial dispersion and improves peak separation. The theoretical analyses discussed earlier were applied to experimental chromatograms of polystyrene latices with very encouraging results.
Keywords: Chemical Engineering; Chemical Engineering